The human rights implications of Australian and Indonesian anti-smuggling laws. (2018) - Kneebone, Susan; Missbach, Antje
In this paper we explain the 'crimmigration' motives - the intersection of criminal law and migration law - of both the Australian and Indonesian Governments and examine the impact and human rights implications of their laws. We show that, in the case of Australia, crimmigration of smuggled asylum seekers was a deliberate policy from the late 1990s onwards, consistent with Australia's stance on transnational crime. In the case of Indonesia, the 'illegality' of asylum seeking and the use of the smuggling trope came about more by default and from a desire to cooperate with Australia. We further show that in both countries the target of anti-smuggling laws is mainly low-level crew and minor players, who are often simple fishermen, many of whom are minors. We explain the hardship that enforcement of anti-smuggling laws causes to fishermen, their families and community.